Asset management policies and guidelines of different states in Australia: A comparative analysis. Issue 3 (1st July 2014) - Nateque Mahmood, Muhammad; Prasad Dhakal, Subas; Brown, Kerry; Keast, Robyn; Wiewiora, Anna
Abstract : Purpose: – The purpose of this paper is to explore and compare the asset management policies and practices of six Australian states – New South Wales, Victoria, Queensland, South Australia, Western Australia and Tasmania – to improve understanding of the policy context to best shape policy focus and guidelines. Australian state-wide asset management policies and guidelines are an emergent policy domain, generating a substantial body of knowledge. However, these documents are spread across the layers of government and are therefore largely fragmented and lack coherency. Design/methodology/approach: – The comparative study is based on the thematic mapping technique using the Leximancer software. Findings: – Asset management policies and guidelines of New South Wales and Victoria have more interconnected themes as compared to other states in Australia. Moreover, based on the findings, New South Wales has covered most of the key concepts in relation to asset management; the remaining five states are yet to develop a comprehensive and integrated approach to asset management policies and guidelines. Research limitations/implications: – This review and its findings have provided a number of directions on which government policies can now be better constructed and assessed. In doing so, the paper contributes to a coherent way forward to satisfy national emergent and ongoing asset management challenges. This paper outlines a rigorous analytical methodology to inform specific policy changes. Originality/value: – This paper provides a basis for further research focused on analyzing the context and processes of asset management guidelines and policies.